MARKETING AND MANAGEMENT UNDER CURRENT CONDITIONS IN UKRAINE: NOOSPHERIC ASPECT OF DEVELOPMENT - Chernov S.I. (Pressing Problems of Public Administration, 2017)
The paper considers the phenomena of marketing and management from the perspective of the regionalnoospheric development theory and its advantages over the theory of sustainable development.The author presents his vision of the processes of forming and implementing a marketing policyin the context of regional noospheric development and use of the socio-cultural potential of publicmanagement under the current conditions of state administration modernizing in the line of publicadministration and information society advancement.